Cocaine use modifies the association between antiretroviral therapy and endothelial dysfunction among adults with HIV infection. Issue 9 (29th May 2019) - Li, Ji; Lai, Hong; Chen, Shaoguang; Kickler, Thomas; Lai, Shenghan
Abstract: Cocaine is commonly used among HIV‐infected people and may worsen HIV disease progression. In addition, existing evidence suggests a link between antiretroviral regimens and endothelial dysfunction. This study aimed to examine whether the associations of antiretroviral therapy (ART) regimens with endothelial dysfunction may be modified by cocaine use in adults with HIV infection. Between 2003 and 2014, 466 HIV‐positive participants residing in Baltimore, Maryland, were enrolled in a study investigating comorbidities associated with HIV/ART. The associations between various risk factors and endothelial dysfunction indicators were examined by robust regression models fitted for the overall subjects and cocaine subgroups, separately. Duration of nonnucleoside reverse‐transcriptase inhibitor (NNRTI)‐based therapy was negatively associated with plasma vWF:Ag levels in cocaine non‐users (β = −.715, SE = .220, P < .05). However, cocaine users on longer‐term NNRTI‐based regimens had greater plasma endothelin‐1 (ET‐1) concentrations than their counterparts (β = .003, SE = .001, P < .05). In addition, current cigarette smoking was significantly positively associated with ET‐1 concentrations in both cocaine non‐users (β = .609, SE = .164, P < .05) and cocaine users (β = .331, SE = .086, P < .05). In conclusion, cocaine use modified the potential effects of NNRTI‐based therapy on biomarkers of endothelial dysfunction. These findings suggested that reduction in cocaine use may improve endothelial function in HIV‐infected cocaine users.